Засоби вимірювання параметрів діелектриків в НВЧ діапазоні методом вільного простору - Гапон, Н. Я. (ХНУРЕ, 2025)
This work is devoted to review of means of measuring dielectric parameters. Among the methods of measuring dielectric parameters, the free space method attracted attention because it is not only non-destructive, but also contactless, which has advantages when measuring heated samples. The use of directional couplers in installations has a long tradition, now it has become automated using embedded microcontrollers, which has made it possible to process using algorithms.
Keywords: діелектрик; метод вільного простору